Pengaruh Pelatihan, Motivasi Kerja, dan Lingkungan Kerja terhadap Kinerja Karyawan Mediterranean Bali - Made Supriyani; Kadek Rai Suwena; I Nengah Suarmanayasa (JURNAL MANAJEMEN MOTIVASI, 2026)
This study aims to analyse the influence of training, work motivation and working environment on the performance of employees at Mediterranean Bali. The study used a quantitative approach with a full sample of 66 staff-level employees. Data were collected via questionnaires and analysed using multiple linear regression. The results of the study showed that training and working environment had a positive and significant effect on employee performance, while work motivation had a negative and significant effect on employee performance. Overall, training, job motivation and working environment significantly affect the performance of Mediterranean Bali employees. Keywords: Training; Motivation; The Working Environment; Employee Performance